A cheap metal for a challenging task: nickel-catalyzed highly diastereo- and enantioselective hydrogenation of tetrasubstituted fluorinated enamides. Issue 1 (16th October 2018) - Guan, Yu-Qing; Han, Zhengyu; Li, Xiuxiu; You, Cai; Tan, Xuefeng; Lv, Hui; Zhang, Xumu
Abstract : Nickel-catalyzed stereospecific syn -selective asymmetric hydrogenation of challenging tetrasubstituted fluorinated enamides has been achieved. This protocol provides an efficient access to chiral α-fluoro-β-amino esters. Abstract : Nickel-catalyzed asymmetric hydrogenation of challenging tetrasubstituted fluorinated enamides has been achieved, affording chiral α-fluoro-β-amino esters in high yields with excellent diastereo- and enantioselectivities (up to 98% yield, >99 : 1 dr, up to >99% ee). Deuterium-labeling experiments and control experiments were conducted to probe the mechanism, and the results indicated that the acidity of the solvent plays a critical role in the control of diastereoselectivity by trapping the adduct of nickel hydride to CC bonds via protonolysis, giving the hydrogenation product with stereospecific syn -selectivity. This protocol provides efficient access to chiral α-fluoro-β-amino esters which have important potential applications in organic synthesis and medicinal chemistry.